(untitled) - Mark Allen Weiss (Redwood City, California, 1994)
The book describes data structures, methods of organizing large amounts of data, nad algorithm analysis, the estimation of the running time of algorithms. Chapter 1 contains review material on descrete math recursion. Chapter 2 deals with algorithm analysis, explains asymtonic analysis and its major weaknesses. Chapter 3 covers lists, stacks, and queues. Chapter 4 covers trees, including external search trees. Chapter 5 is a relatively short chapter concerning hash tables. Chapter 6 is about priority queues. Chapter 7 covers sorting. It is very specific with respect to coding details and analysis. Four algorithms are analyzed in detail: insertion sort, Shellsort, heaosort, and quicksort. Chapter 8 discusses the disjoint set algorithm with proof and the running time. Chapter 9 covers graph algorithms. Chapter 10 covers algorithm design by examining commonproblem-solving techniques. Chapter 11 deals with amortized analysis. Chapter 12 covers search tree algorithms, some multidimensional data structures, and the pairing heap. At the end of each chapter, the book provides the exercises, difficult exercises are marked with an asterisk, and more challenging exercises have two asterisks. References are placed at the end of each chapter. Generally the references either are historical, representing the original source of the material, or they represent extensions and improvements to the results given in the book. Some references represent solution to exercises
Keywords: computer algorithms,data structures ( computer science )